IN SILICO STUDY: SECONDARY METABOLITES FROM RED GINGER RHIZOME (Zingiber Officinale Var. Rubrum) AS POTENTIAL INHIBITORS OF3CLpro AND PLpro OF SARS-CoV-2 - Meilia Suherman; Selvira Anandia Intan Maulidya (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
The COVID-19 outbreak prompted the development of novel drugs to treat the disease. Targeting of virus proteins has attracted great interest in the discovery of COVID-19 drugs. 3CLpro and PLpro are promising targets because of their important role in viral replication. Hence, various efforts have been made to find specific therapeutics for COVID-19, including those derived from plants as anti-Covid-19. Red ginger rhizome (Zingiber officinale var. rubrum) contains secondary metabolites that are known for their health benefits. This in silico study aimed to determine the potency of red ginger rhizome as PLpro and 3CLpro of SARS-CoV-2 inhibitor which may be applied to treat COVID-19. This research was conducted using molecular docking and molecular dynamics simulations. The molecular docking simulation of red ginger compounds in complex with SARS-CoV-2 PLpro showed that 27 compounds have a binding free energy (?G) lower than that of the reference ligand. On the other hand, none of the complexes between red ginger compounds and 3CLpro had a lower binding free energy than the reference ligand. Visualization of interaction features at the PLpro of SARS-CoV-2’s active site shows that secondary metabolites dominantly interact with hydrogen bonds. The ar-curcumene and PLpro complex of SARS-CoV-2 appears very stable and has the lowest flexibility compared to HBA as a native ligand and molnupiravir as a reference ligand based on RMSD and RMSF plot analysis using molecular dynamic simulation...